Distinguishing “Expertise” in te Reo Māori: Tohunga, Pū and Rehe - Mitchell, Kelly Frances (Waka Kuaka, 2021)
This article presents a model that defines and differentiates three varieties of indigenous Māori expertise—tohunga, pū and rehe. The three terms are commonly defined in the modern Aotearoa New Zealand literature—both academic and non-academic—to all mean the same thing, ‘expert’. However, given the importance of knowledge transfer in precolonial society, as well as the established political order in which tohunga are known to historically have played an important role, it seems unlikely that Māori tīpuna ‘ancestors’ would have used the terms interchangeably. Through an analysis of a sample of newspapers, academic works, dictionaries and traditional Māori resources (whakataukī ‘proverbs’, kīwaha ‘idioms’, pūrākau ‘histories and mythologies’), primarily older works but also a small collection of newer examples from academia and governmental resources for comparison, the three terms are defined. I argue that each had unique purposes in traditional Māori society, they were ranked and there were specific requirements for achieving each rank. My aim is to help clarify, communicate and legitimise categories of Māori expertise and their use in a society that is increasingly recognising and asserting indigenous rights and treaty obligations.